The Effect of Institutional Ownership, Managerial Ownership, and Deferred Tax Expense on Earnings Management - Kusumawardhani, Indra; Murdianingrum, Sri Luna (Journal of Governance Risk Management Compliance and Sustainability, 2022)
Earnings are commonly used as one of the measuring instruments to determine firms’ performance. Earnings numbers indicated firms' ability to manage resources and earnings information will be used by users to make decisions related to firms' performance and tax collection. Earnings management practices are mostly influenced by the conflict of interest between principals and agents, but they can be minimized with good corporate governance. The objective of this research is to determine the effect of Institutional Ownership, Managerial Ownership, and Deferred Tax Expense on Earnings Management. Research samples were taken from 383 nonfinancial firms listed on the Indonesia Stock Exchange from 2017 to 2019 by using the purposive sampling technique. The independent variables used in this research were Institutional Ownership, Managerial Ownership, and Deferred Tax Expense, while the dependent variable was Earnings Management. Research results suggested that Institutional Ownership and Managerial Ownership affected Earnings Management, while Deferred Tax Expenses have no effect on Earnings Management